2019
DOI: 10.2174/1389201020666190211145215
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Crude Glycerol, Residue Deriving from Biodiesel- Production Process, with the Use of Wild-type New Isolated Yarrowia lipolytica Strains: Production of Metabolites with Pharmaceutical and Biotechnological Interest

Abstract: Background & Objective: Crude glycerol (Glol), used as substrate for screening eleven natural Yarrowia lipolytica strains in shake-flask experiments. Aim of this study was to assess the ability of the screened strains to produce biomass (dry cell weight; X), lipid (L), citric acid (Cit), mannitol (Man), arabitol (Ara) and erythritol (Ery), compounds presenting pharmaceutical and biotechnological interest, in glycerol-based nitrogen-limited media, in which initial glycerol concentration had been adjusted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 61 publications
1
4
0
2
Order By: Relevance
“…Total cellular lipids were converted into their corresponding FAMEs, and cellular fatty acid (FA) composition analysis was performed for the late growth phase in the case of the shake-flask cultures, and throughout the culture, for the fed-batch bioreactor experiment (Table 6). In general, FA composition of total lipids of the strain LMBF Y-46 presented important similarities with those reported for various other Y. lipolytica strains cultivated in batch flask and bioreactor cultures, during growth on glycerol or similarly metabolized compounds, under nitrogen limitation [8,16,18,19,21,22,38,40,49,53]. Specifically, the yeast lipids were mainly composed of the FAs oleic (C18:1), palmitic (C16:0), palmitoleic (C16:1), stearic (C18:0) and linoleic (C18:2).…”
Section: Cellular Lipids Of Yarrowia Lipolytica Lmbf Y-46supporting
confidence: 71%
See 2 more Smart Citations
“…Total cellular lipids were converted into their corresponding FAMEs, and cellular fatty acid (FA) composition analysis was performed for the late growth phase in the case of the shake-flask cultures, and throughout the culture, for the fed-batch bioreactor experiment (Table 6). In general, FA composition of total lipids of the strain LMBF Y-46 presented important similarities with those reported for various other Y. lipolytica strains cultivated in batch flask and bioreactor cultures, during growth on glycerol or similarly metabolized compounds, under nitrogen limitation [8,16,18,19,21,22,38,40,49,53]. Specifically, the yeast lipids were mainly composed of the FAs oleic (C18:1), palmitic (C16:0), palmitoleic (C16:1), stearic (C18:0) and linoleic (C18:2).…”
Section: Cellular Lipids Of Yarrowia Lipolytica Lmbf Y-46supporting
confidence: 71%
“…Moreover, it is interesting to indicate that the maximum volumetric productivity of CA (P CAmax ) achieved in the current batch culture (P CAmax calculated as P CAmax = CA max ∆t , where ∆t is the fermentation time in the batch or fed-batch culture requested to achieve this CA max value) was ≈0.65 g/L/h, being certainly comparable with the highest values reported by other wild-type or mutant Y. lipolytica strains cultivated in batch (0.52-0.85 g/L/h [55]), fed-batch (i.e., 0.40-0.93 g/L/h [56][57][58][59]), and continuous (between 0.70 and 1.30 g/L/h [60]) bioreactor operations (in the cited batch and fed-batch cultures, P CAmax was calculated as in the present study, whereas in the continuous cultures, P CA was calculated as P CA = CA • D, where CA was the concentration at the steady-state and D was the dilution rate imposed). It is noted that in the shake-flask citric acid production experiments, the achieved productivities (calculated as previously stated) are, in general, much lower (0.07-0.25 g/L/h) [8,19,23,40,49,53,61,62].…”
Section: Metabolic Characterization Of Yarrowia Lipolytica Lmbf Y-46:...mentioning
confidence: 54%
See 1 more Smart Citation
“…This value is higher than those obtained in a glucose-based medium, suggested that OMW triggers CA synthesis and this waste stream could be used as a co-substrate for CA production. Using a mixture of OMW and crude glycerol, the strain ACA-DC 5029 produced CA with a resultant titer of 79 g/L and yield from glycerol of 0.46 g/g in 528 h [32]. For the Y. lipolytica strain ACA-YC 5031, addition of NaCl (%) in OMW-based media significantly increases CA production with titer and yield from glycerol of 54 g/L and 0.82 g/g, respectively [33].…”
Section: Citric Acidmentioning
confidence: 99%
“…Микроорганизмы на определенных составах питательной среды обладают высокой скоростью роста и способностью синтезировать спектр питательных соединений: белков, липидов, углеводов, каротиноидов, витаминов и т. д. [51,52]. Биомасса микроорганизмов может использоваться в составе рационов сельскохозяйственных животных и птицы для повышения продуктивности, а в питании человека -для получения новых источников белков.…”
Section: Introductionunclassified